Benefits of Additional Make-to-Stock Channel with Price Control Characteristic to Make-to-Order Channel - Hyun-cheol Paul Choi (International Journal of Supply Chain Management, 2014)
In this paper we study the benefits for a manufacturer or supplier of having a secondary sales channel with price control in addition to its primary sales channel. Our definition of the primary sales channel is that a majority of companys total profit is from it, and that the company has make-to-order (MTO) production environment to meet this demand. On the other hand, our definition of the secondary channel is that the company is assumed to be able to create certain demands by reducing the price of standard products for the channel. Therefore, the secondary channel is supplied by make-to-stock (MTS) products as a manufacturer tries to make use of excess capacity after meeting the demand for the primary channel. We assume that the manufacturer can create just enough volume of demand from the secondary channel to match the excess production capacity. We call the primary channel MTO, and the secondary MTS. In other words, a manufacturer or supplier can increase revenues/profits and smooth the MTO productions by using the MTS channel through utilizing the excess capacity. However, developing MTS channel needs investments. In this paper, we try to find out in what operational characteristics a company can justify the investments for the benefits of developing the additional MTS channel to the existing MTO channel. We measure the quantitative benefits of the additional channel over various sets of operational characteristics and interpret the results. With a set of experiments, we investigate the effect of demand variability, capacity utilization, and holding and other production-related costs with a simple price-demand relationship. We have observed that benefits increase as demand variability increases, as capacity utilization decreases, and as capacity change costs. However, the holding does not seem to impact the benefits.